From groove binding to intercalation: unravelling the weak interactions and other factors modulating the modes of interaction between methylated phenanthroline-based drugs and duplex DNA. Issue 47 (26th November 2021) - Sánchez-González, Ángel; Castro, Tarsila G.; Melle-Franco, Manuel; Gil, Adrià
Abstract : Substitution in number and position may modulate the interaction of ligands with DNA. Depending on the weak interactions produced by substitution and solvent effects the transition from groove binding to intercalation may be easy or difficult. Abstract : Several antitumor drugs base their cytotoxicity on their capacity to intercalate between base pairs of DNA. Nevertheless, it has been established that the mechanism of intercalation of drugs in DNA starts with the prior groove binding mode of interaction of the drug with DNA. Sometimes, for some kind of flat small molecules, groove binding does not produce any cytotoxic effect and the fast transition of such flat small molecules to the cytotoxic intercalation mode is desirable. This is the case of methylated phenanthroline (phen) derivatives, where, changes in the substitution in the position and number of methyl groups determine their capability as cytotoxic compounds and, therefore, it is a way for the modulation of cytotoxic effects. In this work, we studied this modulation by means of the interaction of the [Pt(en)(phen)] 2+ complex and several derivatives by methylation of phen in different number and position and the d(GTCGAC)2 DNA hexamer via groove binding using PM6-DH2 and DFT-D methods. The analysis of the geometries, electronic structure and energetics of the studied systems was compared to experimental works to gain insight into the relation structure-interaction for the studied systems with cytotoxicity. The trends are explained by means of the Non-Covalent Interaction (NCI) index, the Energy Decomposition Analysis (EDA) and solvation contributions. Our results are in agreement with the experiments, in which the methylation of position 4 of phen seems to favour the interaction via groove binding thus making the transition to the intercalation cytotoxic mode difficult. Looking at the NCI results, these interactions come not only from the CH/π and CH/n interactions of the methyl group in position 4 but also from the ethylenediamine (en) ligand, whose orientation in the Pt complex was found in such a way that it produces a high number of weak interactions with DNA, especially with the sugar and phosphate backbone.